The Key Heterolysis Selectivity of Divalent Sulfur–Sulfur Bonds for a Unified Mechanistic Scheme in the Thiosulfatolysis and Sulfitolysis of the Pentathionate Ion. Issue 35 (11th November 2016) - Ji, Chen; Yan, Xiangdong; Pan, Changwei; Lv, Fengpeng; Gao, Qingyu
Abstract : The thiosulfatolysis and sulfitolysis of pentathionate were studied in the pH ranges 4.50–8.0 and 4.0–5.0 at T = (25.0 ± 0.1) °C by HPLC monitoring of the time‐dependence and distribution of different sulfur species. The two systems are first order with respect to both reactants. In contrast to tetrathionate, pentathionate and higher polythionates contain inequivalent divalent sulfur atoms; therefore, the complexity of the mechanism increases. The selective heterolytic cleavages of sulfur–sulfur bonds are essential steps for the time evolution and equilibrium distribution of the divalent sulfur species. A proposed eight‐step mechanistic model, which incorporates the proton equilibrium of sulfite and the heterolytic cleavage of divalent sulfur–sulfur bonds of hexathionate, was applied to evaluate the thiosulfatolysis and sulfitolysis of the pentathionate ion, and the kinetics of both systems are modulated by this mechanistic network. Abstract : The selective heterolytic cleavages of sulfur–sulfur bonds are essential mechanistic steps for nucleophilic attacks on pentathionate and higher spolythionate ions containing inequivalent divalent sulfur atoms.